2010
DOI: 10.1007/s10570-010-9463-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of natural rubber nanocomposites reinforced with cellulosic nanoparticles obtained from combined mechanical shearing, and enzymatic and acid hydrolysis of sisal fibers

Abstract: In a previous work (Siqueira et al. 2010b) the preparation of cellulosic nanoparticles from sisal fibers using different processing routes, viz. a combination of mechanical shearing, acid and enzymatic hydrolysis was reported. It was shown that the preenzymatic hydrolysis treatment of bleached sisal pulp helps the preparation of well individualized rod-like nanocrystals. An amorphous polymer (natural rubber-NR) was chosen as model matrix to investigate the effect of these nanoparticles on the thermomechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 12 publications
2
51
3
4
Order By: Relevance
“…In the recent years, NR-based nanocomposites with biobased nanoreinforcements like nanowhiskers extracted from wheat straw, Syngonanthus nitens (Capim dourado), rachis of palm tree, sisal, bagasse, chitin, etc. are found in the literature (Hajji et al 1996;Bendahou et al 2009;Siqueira et al 2010Siqueira et al , 2011Bras et al 2010;Nair and Dufresne 2003). Most of these studies deal with natural rubber latex-based nanocomposites prepared by casting and no attempts to develop vulcanized NR-based nanocomposites have been reported.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the recent years, NR-based nanocomposites with biobased nanoreinforcements like nanowhiskers extracted from wheat straw, Syngonanthus nitens (Capim dourado), rachis of palm tree, sisal, bagasse, chitin, etc. are found in the literature (Hajji et al 1996;Bendahou et al 2009;Siqueira et al 2010Siqueira et al , 2011Bras et al 2010;Nair and Dufresne 2003). Most of these studies deal with natural rubber latex-based nanocomposites prepared by casting and no attempts to develop vulcanized NR-based nanocomposites have been reported.…”
Section: Introductionmentioning
confidence: 86%
“…Nanocelluloses, which typically have a width of 5 to 50 nm and a high specific surface area, have seen rapid advancement and considerable interest in the last decade owing to their renewable character, advantageous mechanical properties, low density, availability, and diversity of sources (Favier et al 1995;Samir et al 2005;Dufresne 2006;Jonoobi et al 2010;Henriksson et al 2007;Bendahou et al 2009;Bras et al 2010;Siqueira et al 2011). In the recent years, NR-based nanocomposites with biobased nanoreinforcements like nanowhiskers extracted from wheat straw, Syngonanthus nitens (Capim dourado), rachis of palm tree, sisal, bagasse, chitin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, is possible to highlight nanocomposites such as poly(3-hydroxybutyrate)(PHB)/bacterial cellulose [7], polyvinyl acetate/sisal cellulose whiskers [8], natural rubber/cellulosic nanoparticles of sisal fibers [9], thermoplastic starch/cellulose nanofibrils from wheat straw [10], poly (oxyethylene)/ramie whiskers [11], and pea starch/cellulose whiskers from pea hull fiber [12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to utilize nanocellulose as a reinforcing phase to form nanocomposites, the strong hydrogen bonding between cellulose crystals must be separated and dispersed well in the polymer matrices [5]. Extensive research has been reported to extract nanocellulose from different sources [6][7][8][9][10]. Typical processes involve mechanical and chemical treatments.…”
Section: Introductionmentioning
confidence: 99%